MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN HABITS OF MIND MAHASISWA MELALUI PEMBELAJARAN DENGAN PENDEKATAN INDUKTIF - Dina Mayadiana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : The research was a quasi-experimental study to measure the ability of Critical Thinking Mathematically (CTM) and the Habits of Mind (HOM) of the students candidates of elementary school teachers. Students who become research subjects are grouped into students having Inductive Learning (IL) and Conventional Learning (CL). CTM test instruments and scales used HOM after tested and fit for use for this study. Analysis of the data showed: (1) CTM students who obtain an IL is better than that obtained CL, (2) HOM students who obtain an IL is better than that obtained CL, and (3) The association between CTM and HOM belongs to adequate criteria. Key words: Thinking, Learning, and Students.